1993
DOI: 10.1021/ac00065a022
|View full text |Cite
|
Sign up to set email alerts
|

Carbon aerogel composite electrodes

Abstract: The electrochemical behavior and analytical performance of new vitreous carbon aerogel composite electrodes are described. These new composite electrodes rely on the unique open-cell nanostructure of aerogel materials, including their interconnected porosity, ultrafine pore sizes (<50 nm), and huge surface area. Transmission and scanning electron microscopies are used to shed useful insights into the carbon network. The enhanced diffusional flux results in a sigmoidal voltammetric response and nonlinear i vs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…This optimized nanotube network could then be backfilled with a host material. For example, we found that immersing the aerogel in a liquid led to complete impregnation of the aerogel through a "wicking" [20] or infiltration [21] process. The liquid could be a polymer or other material that could be subsequently cured to form a solid composite.…”
mentioning
confidence: 99%
“…This optimized nanotube network could then be backfilled with a host material. For example, we found that immersing the aerogel in a liquid led to complete impregnation of the aerogel through a "wicking" [20] or infiltration [21] process. The liquid could be a polymer or other material that could be subsequently cured to form a solid composite.…”
mentioning
confidence: 99%
“…Since the temperature differential between the hot and cold side of the heat transfer surface is only 7-9 'F (4-5 "C), the required energy and rates of scale formation are both low. A typical MVC system consumes - [30][31][32][33][34][35][36][37][38][39][40][41]. See Table 1 for published energy requirements for SW desalination processes [2].…”
Section: Thermal Processesmentioning
confidence: 99%
“…Note that thermal and chemical activation has been used to achieve BET surface areas of 1.3x107 ft2 lb-l (2600 m2 g-*) [32]. Resorcinol-formaldehyde (RF) aerogels and their carbonized derivatives were first developed by LLNL [33][34][35][36]. Monolithic sheets of this material were made by inlltrating a resorcinolformaldehyde solution into a porous carbon paper (Textron Specialty Materials, Lowell, MA), curing the wetted paper between glass plates in a closed vessel, and then pyrolyzing in an inert atmosphere.…”
Section: Carbon Aerogel Electrodesmentioning
confidence: 99%
“…In contrast, the differential pressure across four stacks in series As previously discussed, electrodes are made from thin sheets of CAC glued to titanium plates with conductive epoxy. Carbon aerogels were developed at Lawrence Livermore National Laboratory and are synthesized by the polycondensation of resorcinol and formaldehyde in a slightly basic medium, followed by supercritical dryins and pyrolysis in an inert atmosphere [26,27]. Sheets of CAC are made by impregnating carbon cloth with the resorcinol-formaldehyde solution and then carbonizing.…”
Section: 1~0~mentioning
confidence: 99%